2019
DOI: 10.1016/j.rmcr.2019.100939
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary lophomoniasis: A rare cause of pneumonia in an immunosuppressed host

Abstract: Bronchopulmonary lophomoniasis is rare but immunocompromised individual is susceptible to this infection. We reported a case of bronchopulmonary lophomoniasis in a Malaysian female with systemic lupus erythromatosus. She presented with productive cough, shortness of breath and high-grade fever for 2 weeks. Physical examination revealed bronchial sound and crackles over the left lung with, reduced expansion and dull percussion in lower left lobe. Chest radiography showed consolidation of the left lung. Routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…Also, Woerden et al 18 found that flagellated protozoa in sputum are more prevalent in asthmatic patients who received corticosteroids compared to the control group. Wahid et al 19 presented Lophomonas in a 29‐year‐old female with systemic lupus erythromatosus. Although many studies have reported eosinophilia as the main result in CBC, but it was not seen in our patient which could be due to her immunocompromised state, 16,20 which is consistent with Wahid et al report 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, Woerden et al 18 found that flagellated protozoa in sputum are more prevalent in asthmatic patients who received corticosteroids compared to the control group. Wahid et al 19 presented Lophomonas in a 29‐year‐old female with systemic lupus erythromatosus. Although many studies have reported eosinophilia as the main result in CBC, but it was not seen in our patient which could be due to her immunocompromised state, 16,20 which is consistent with Wahid et al report 19 .…”
Section: Discussionmentioning
confidence: 99%
“…SLE patients are also at increased risk for tuberculosis and infections with non-tuberculous mycobacteria [ 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Protozoa infections, also with rare pathogens such as Lophomonas blattarum, have been reported [ 127 ].…”
Section: Infectionsmentioning
confidence: 99%
“…O primeiro caso de Lofomoníase pulmonar foi reportado em 1993 (Muñoz et al, 2019), e atualmente pouco mais de 250 casos de infecção por Lspp foram descritos (Wahid et al, 2019). A maior parte dos relatos ocorreu na China, e em outros países como Turquia, Peru, Índia, México, Irã e Espanha (Tyagi et al, 2016;Wahid et al, 2019).…”
Section: Introductionunclassified
“…O primeiro caso de Lofomoníase pulmonar foi reportado em 1993 (Muñoz et al, 2019), e atualmente pouco mais de 250 casos de infecção por Lspp foram descritos (Wahid et al, 2019). A maior parte dos relatos ocorreu na China, e em outros países como Turquia, Peru, Índia, México, Irã e Espanha (Tyagi et al, 2016;Wahid et al, 2019). Em geral, os casos descritos estão associados a diversas condições de imunossupressão, como uso prolongado de corticosteroides, doença pulmonar crônica em atividade, diabetes mellitus, antecedente de transplante renal, hepático ou de medula óssea (Xue et al, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation